Influence of Voltage Value on Operational Mode of Outdoor Lighting Grid Network - V. B. Kozlovskaya; V. N. Kalechits (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper draws attention to specific features of the modes pertaining to operation of outdoor lighting lines. An outdoor lighting line is sensitive to voltage fluctuations. The voltage value has a significant effect on the electricity consumption indices and operational characteristics of various lamps. Efficiency and operational conditions of outdoor lighting luminaires are determined by an operational  mode of  a network. Calculation of electrical parameters pertaining to outdoor lighting power network has some specific features.